Prevalence of Hepatitis-B and Hepatitis-C among Blood donors in Sulaimani City - Mohammad, Mohammad O. (Sulaimani Journal for Pure and Applied Sciences, 2007)
This is a prospective study conducted inJanuary-May 2002'.Blood Samples from l514 healthy blood donors were screened for hepatitis B and t *p"tiiit C in Sulaimani main blood bank' Enzyme Linked Immune Sorbent Assay (ELISA) iechnique ;;;; io detect Hepatitis B Surface Antigen (HBsAg) and Anti Hepatitis C Virus Antibody (Anti HCV euj. ine prevalence rate of HBsAg and anti'HCV Ab was 23%,1:2 o/o respectively in the blood donors'
Keywords: Hepatitis B; Hepatitis C; Sulaimani blood donors